The influence of additives on the delivery of paclitaxel from bioresorbable PLGA films - Huang, Charlotte Liwen. (2013)
The study of the influences of additives on the drug delivery characteristics from PLGA thin films as a coating on angioplasty balloons was reported in this thesis. The objective is to investigate the use of additives as a means to control and modulate the delivery of paclitaxel from PLGA thin films. The release profiles obtained from the first part of the study with different types of PLGA show linear dependence on the concentration of terminal carboxylic acid end-groups of PLGA, which also regulates the degradation of PLGA films. The concentration of these end-groups is determined by the molecular weight of PLGA. The changes in molecular weight of PLGA resulted in changes in the hydration and mechanical behavior of these bioresorbable polyester thin films. However, despite the immiscibility and phase separation with the incorporation of additives with PLGA through blending, the mechanical properties of the PLGA films evaluated under simulated physiological conditions were not affected. The hydration of PLGA films played an important role in influencing the rate of hydrolytic degradation and drug release behavior. The incorporation of long chain additives with PLGA resulted in large phase-separated domains which gave rise to large pores, high mass loss and high initial burst release of paclitaxel from the dissolution and leaching of additives upon hydration. The degradation rates of PLGA were reduced by the diffusion of the acidic by-products through these large water-filled pores, which would have otherwise accumulated and contributed to the autocatalysis of PLGA. The incorporation of short chain additives with PLGA resulted in high hydration rates and high paclitaxel release rates. While paclitaxel and additives were preferentially co-localized, a statistical correlation was established between the release of paclitaxel and the leaching of additives upon hydration that can be sustained, controlled and modulated based on the concentration, molecular weight and the functionality of additives.